Professional perspectives on multimodal communication in the development of the subject with deafblindness - Da Mata, Simara Pereira [UNESP]; Soriano, Karen Regiane [UNESP]; De Oliveira, Jáima Pinheiro [UNESP] (FapUNIFESP (SciELO), 2021)
Communication is the basis for any person’s teaching and learning process. For the deafblind subject, especially of the congenital nature, it is a permanent challenge that demands of the professionals a specific knowledge, adequate and well-founded performance. Thus, this study aimed to identify, from the perspective of professionals who worked with a subject with congenital deafblindness, aspects of use of the remaining pathways, simultaneous or isolated, for the establishment of communication. For that, based on the principles of a qualitative descriptive research, the semi-structured interview procedure was used as data collection. The interviews were transcribed in full and treated from their content to obtain subthemes that were later grouped and converted into categories. Specifically for this analysis, the category presented was the Multimodal Communication. Data analysis allowed to identify the professionals’ perspectives regarding the use of simultaneous or isolated remnant pathways, in order to favor the establishment of a communication. In general, it was observed that the participants’ perspectives were related to the combination of ways of anticipating activities and/or actions through the use of different sensory pathways, with a predominance of gustatory and olfactory senses, while proprioceptive and kinesthetic were described in a smaller proportion.
Perspectivas de profissionais sobre a comunicação multimodal no desenvolvimento de um sujeito com surdocegueira
Keywords: Educational Inclusion; Sensorial communication; Special Education